Hansel and gretel: read it yourself - Pound, Claire (Ladybird Books London, 2009)
Hansel and Gretel is a well-loved tale of siblings working together. This is a Level Three tale for children who are developing reading confidence and stamina, and who are ready to progress to longer stories. 4-7 yrs